Veterinary practice in domestic dogs as a risk factor for Toxocara canis In Lima, Peru - Anacleto N., Lady (2015)
The frequency of seropositives and risk of exposure to Toxocara canis in the personnel working in veterinary clinics in the city of Lima was determined. An exposed group with direct contact to dogs (n=135) and a non-exposed group of administrative staff (n=108) were evaluated. Sera samples were analyzed by ELISA test using excretion/ secretion antigens of L2 larvi of T. canis in dilutions of 1/200, 1/400, 1/800, 1/1600 and greater than 1/1600, searching for IgG antibodies. In the exposed group, 95.6, 58.5, 37.0, 23.7 y 9.6% resulted positive in the dilutions studied, respectively, and in the non-exposed group 97.2, 50.0, 32.4, 17.6 y 3.7% resulted positive respectively. No association was found between the proportion of positives and the two groups. It was concluded that the professional practice does not represent a risk factor for the occurrence of human infections by T. canis.